Bioactive molecules derived from smoke and seaweed Ecklonia maxima showing phytohormone-like activity in Spinacia oleracea L - Kulkarni, Manoj G; Rengasamy, Kannan R R; Pendota, Srinivasa C; Gruz, Jiří; Plačková, Lenka; Novák, Ondřej; Doležal, Karel; Van Staden, Johannes (New biotechnology, 2019)
Bioactive compounds such as karrikinolide (KAR1 from smoke) and eckol (from the seaweed Ecklonia maxima) show promising effects on several important crop plants. These plant growth-stimulating organic biomolecules, along with crude extracts (smoke-water and Kelpak® product prepared from Ecklonia maxima), were tested on spinach plants. Eckol sprayed at 10-6 M significantly increased all the growth and biochemical parameters examined compared to control spinach plants. All tested plant growth biostimulants significantly increased total chlorophyll, carotenoids and protein content of spinach leaves. The cytokinin profile of spinach plants was also determined. Cis-zeatin, dihydrozeatin and isopentenyladenine types of cytokinins were promoted by both smoke- and seaweed-based biostimulants. In comparison to the control plants, the level of free sinapic acid was greater in all spinach plants treated with these biostimulants. The application of these biostimulants can help spinach crop by improving growth, yield and nutritional quality; moreover, they are organic and cost-effective.
Keywords: Phytohormones; pyrany; zemědělské plodiny; Hydroxybenzoates; kouř; Furans; Phaeophyceae; Pyrans; Crops, Agricultural; Spinacia oleracea; cytokininy; Cytokinins; Biostimulants; furany; Leafy vegetables; mořské řasy; Growth; Dioxins; regulátory růstu rostlin; Smoke; dioxiny; hydroxybenzoáty; Seaweed; Plant Growth Regulators